The range of multiple sclerosis associated with neurofibromatosis type 1. Issue 5 (1st November 2001) - Perini, P; Gallo, P
Abstract : Multiple sclerosis associated with neurofibromatosis type 1 (NF1) is a very rare event. Seven patients with multiple sclerosis and NF1 are described in the literature, and all were reported to have the primary progressive form of multiple sclerosis. Three new patients with NF1 that developed multiple sclerosis are described and it is shown that the range of multiple sclerosis associated with NF1 includes the relapsing forms of the disease. The risk of having both NF1 and multiple sclerosis in north east Italy is higher than would be expected based on the prevalence rates of the two diseases.